2004
DOI: 10.1017/cbo9781139524827
|View full text |Cite
|
Sign up to set email alerts
|

Research Genres

Abstract: This book provides a rich and accessible account of genre studies by a world-renowned applied linguist. The hardback edition discusses today's research world, its various configurations of genres, and the role of English within the genres. Theoretical and methodological issues are explored, with a special emphasis on various metaphors of genre. The book is full of carefully worded detail and each chapter ends with suggestions for pedagogical practice. The volume closes with evaluations of contrastive rhetor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
458
0
179

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,155 publications
(645 citation statements)
references
References 0 publications
8
458
0
179
Order By: Relevance
“…He cited Swales' analysis of a typical article introduction as consisting of a four-move structure, namely, establishing the research field, summarizing previous research, preparing for present research, and introducing the present research. Applying the work of Swales (2004Swales ( , 1990, Kanoksilapatham (2009), studying prevalent organizational patterns as manifested in scientific research article abstracts, observed that the use of such moves could be recognized with some variations. Nuttall (2000) differentiates four types of meaning when a text is processed.…”
Section: Review Of Literaturementioning
confidence: 99%
“…He cited Swales' analysis of a typical article introduction as consisting of a four-move structure, namely, establishing the research field, summarizing previous research, preparing for present research, and introducing the present research. Applying the work of Swales (2004Swales ( , 1990, Kanoksilapatham (2009), studying prevalent organizational patterns as manifested in scientific research article abstracts, observed that the use of such moves could be recognized with some variations. Nuttall (2000) differentiates four types of meaning when a text is processed.…”
Section: Review Of Literaturementioning
confidence: 99%
“…For example, students of literature and linguistics need to be taught academic essay writing, so that they are competent in writing essays and compositions that pertain to a general and wide area of topics requiring creativity and independence. Writing in English is essentially an evolving process that takes into consideration the linguistic, cognitive, social, and cultural aspects, which demands a multidimensional approach (Kucer & Silva, 2006) to achieve effective written communication in order to meet the expectations of a certain discourse community (Swales, 1990(Swales, , 2004. Writers employ certain cognitive strategies in the process of writing, like planning the essay and reviewing and proofreading, in order to construct meaning.…”
Section: Discussionmentioning
confidence: 99%
“…Then, publications are predicted to rise because of the contribution given by scholars from India (Benfield & Howard, 2000;Ferguson, 2007; clac 57/2014, 45-58 cianflone: communicating 49 Hyland, 2009;Salager-Meyer, 2008;Ware & Mabe, 2009). These academics often leave their home countries to be enrolled in leading UK and US universities to gain the "been to America" status once back home (Swales, 2004). To this, the involvement of researchers from the so called emerging countries, namely China, South Korea, Taiwan and Singapore, not to talk of Latin America, should be added.…”
Section: Data On Publication Outputmentioning
confidence: 99%
“…This role of English has an impact on the editorial practices of many journals, too. As a necessity, in fact, many European and non-European journals to keep pace with this "English-driven" trend and to gain international reputation and world-wide readership within the increasingly globalized audience, have adopted the editorial strategy of selecting English as the official language of publication (Swales, 2004). Some journals have also translated the title in English.…”
Section: The Predominance Of English In Scholarly Publicationsmentioning
confidence: 99%
See 1 more Smart Citation